2021
DOI: 10.1186/s13046-021-01838-5
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SNHG14 promotes hepatocellular carcinoma progression by regulating miR-876-5p/SSR2 axis

Abstract: Background Aberrant expressions of long noncoding RNAs (lncRNAs) have been demonstrated to be related to the progress of HCC. The mechanisms that SNHG14 has participated in the development of HCC are obscure. Methods Quantitative real-time PCR (qRT-PCR) was used to measure the lncRNA, microRNA and mRNA expression level. Cell migration, invasion and proliferation ability were evaluated by transwell and CCK8 assays. The ceRNA regulatory mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…(36,37). In HCC, miR-876-5p acts as the targets of LncRNA PITPNA-AS1, long noncoding RNA SNHG14, and LINC-ROR and then regulates proliferation and sorafenib sensitivity of HCC (38)(39)(40). miR-876-5p also suppresses HCC progression by targeting DNMT3A and inhibits EMT and metastasis of HCC by targeting BCL6 corepressor like 1 (BCORL1) (36,41).…”
Section: Discussionmentioning
confidence: 99%
“…(36,37). In HCC, miR-876-5p acts as the targets of LncRNA PITPNA-AS1, long noncoding RNA SNHG14, and LINC-ROR and then regulates proliferation and sorafenib sensitivity of HCC (38)(39)(40). miR-876-5p also suppresses HCC progression by targeting DNMT3A and inhibits EMT and metastasis of HCC by targeting BCL6 corepressor like 1 (BCORL1) (36,41).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the expression level of SNHG14 has been demonstrated correlated with prognosis in patients with NSCLC ( Zhang et al, 2019d ), HCC ( Zhang H. et al, 2020 ), ovarian cancer ( Zhao J. L. et al, 2019 ), retinoblastoma ( Sun et al, 2020 ), pancreatic ductal adenocarcinoma ( Xie et al, 2020 ), colorectal cancer ( Pei et al, 2019 ), cervical cancer ( Ji et al, 2019 ), and endometrial cancer ( Zhao et al, 2020 ). Furthermore, some researchers discovered that highly expressed SNHG14 was positively correlated with large tumor size, advanced TNM stage, distant metastasis and poor tumor differentiation in bladder cancer ( Feng et al, 2021 ), NSCLC ( Zhang et al, 2019d ), HCC ( Liao et al, 2021 ), prostate cancer ( Luo et al, 2020 ), retinoblastoma ( Sun et al, 2020 ), pancreatic cancer ( Deng et al, 2019 ), and cervical cancer ( Ji et al, 2019 ). The results indicate that SNHG14 can become a prognostic indicator of cancers.…”
Section: Clinical Relevance Of Small Nucleolar Rna Host Gene 14 In Cancersmentioning
confidence: 99%
“…As for biological function, the overexpression of this lncRNA accelerated cell proliferation, invasion, and migration and suppressed cell apoptosis. Conversely, knockdown of SNHG14 could cause the exact opposite effects on HCC cells ( Pu et al, 2019 ; Tang and Yang, 2020 ; Xu X. et al, 2020 ; Zhang H. et al, 2020 ; Liao et al, 2021 ). Mechanistic investigations demonstrated that SNHG14 functions as a competing endogenous RNA and sponged miRNAs, such as miR-4673, miR-217-5p, miR-656-3p, and miR-876-5p ( Pu et al, 2019 ; Tang and Yang, 2020 ; Zhang H. et al, 2020 ; Liao et al, 2021 ).…”
Section: Biology Function and The Molecular Mechanism Of Small Nucleolar Rna Host Gene 14 In Various Cancersmentioning
confidence: 99%
See 2 more Smart Citations